System analysis and process redesign for quality improvement of sepsis resuscitation. (16th October 2014) - Alqudah, Sura K.; Dong, Yue; Lu, Huitian; Lu, Susan
Severe sepsis and septic shock are serious medical emergencies that require timely treatment. The Sepsis Resuscitation Bundle was implemented to frame the resuscitation time within 6 h of onset. Missing this goal has a major impact on treatment outcomes and cost. This study demonstrates the potential of applying a systems engineering approach to improve resuscitation compliance. Root cause analysis, an industrial engineering tool, was used to analyse the existing process and identify sources of delay. Simulation modelling was performed to study event dynamics and propose alternatives. Sensitivity analysis was used to test the proposed alternatives. Results showed that improvements could be achieved by adopting major event adjustments. Applying these adjustments is projected to increase compliance from 50% to 71% and reduce average patient cycle time by 32%, improving the quality of sepsis and septic shock resuscitation in the ICU.